Enhanced DQE and sub-pixel resolution by single-event processing in counting hybrid pixel electron detectors: A simulation study - Zambon, P. (Frontiers in Physics, 2023)
The detective quantum efficiency (DQE) is prominent figure of merit for imaging detectors and its optimization is of fundamental importance for an efficient use of the experimental apparatus. In this work, Istudy the potential improvement offered by data processing on a single-event basis, in a counting hybrid pixel electron detector (HPD). In particular, I introduce a simple and robust method of single-event processing based on the substitution of the original cluster of pixels with an isotropic Gaussian function. Key features are a better filtering of the noise power spectrum (NPS) and to readily allow for sub-pixel resolution. The performance of the proposed method is compared to other standard techniques like centroiding and event normalization, in the simulated realistic scenario of 100 keV electrons impinging on a 450 um-thick silicon sensor with a pixel size of 75 um, yielding the best results. The DQE can potentially be enhanced over the entire spatial frequency range, increasing from 0.86 to nearly 1 at zero frequency and extending up to 1.40 times the physical Nyquist frequency of the system thanks to the sub-pixel resolution capability.